2009
DOI: 10.1016/j.stem.2009.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Synergy between CD26/DPP-IV Inhibition and G-CSF Improves Cardiac Function after Acute Myocardial Infarction

Abstract: Ischemic cardiomyopathy is one of the main causes of death, which may be prevented by stem cell-based therapies. SDF-1alpha is the major chemokine attracting stem cells to the heart. Since SDF-1alpha is cleaved and inactivated by CD26/dipeptidylpeptidase IV (DPP-IV), we established a therapeutic concept--applicable to ischemic disorders in general--by combining genetic and pharmacologic inhibition of DPP-IV with G-CSF-mediated stem cell mobilization after myocardial infarction in mice. This approach leads to (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
216
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 278 publications
(227 citation statements)
references
References 54 publications
7
216
0
4
Order By: Relevance
“…30,31 Zaruba et al reported that pharmacologic inhibition of DPP-4 was able to increase the homing of SDF-1 receptor-positive endothelial progenitor cells at sites of myocardial damage in mice, thereby reducing cardiac remodeling, functional improvement, and survival. 32 However, plasma SDF-1 levels in mice treated by the DPP-4 inhibitor were lower than in untreated mice, indicating that plasma SDF-1 might play no role in renal protection by AG. As described above, the SDF-1-CXC receptor 4 (CXCR4) pathway mediates migration of resting hematopoietic progenitors.…”
Section: Discussionmentioning
confidence: 96%
“…30,31 Zaruba et al reported that pharmacologic inhibition of DPP-4 was able to increase the homing of SDF-1 receptor-positive endothelial progenitor cells at sites of myocardial damage in mice, thereby reducing cardiac remodeling, functional improvement, and survival. 32 However, plasma SDF-1 levels in mice treated by the DPP-4 inhibitor were lower than in untreated mice, indicating that plasma SDF-1 might play no role in renal protection by AG. As described above, the SDF-1-CXC receptor 4 (CXCR4) pathway mediates migration of resting hematopoietic progenitors.…”
Section: Discussionmentioning
confidence: 96%
“…Therapeutic efficacy may thus be improved by optimizing tissue retention and stability of the delivered proteins [105][106][107] . For instance, administration of Diprotin A, a pharmacologic inhibitor of DPP, enhanced the stability of SDF-1, which increased myocardial homing of CXCR4 + progenitor cells and function [108,109] . Thus, a potential strategy to boost the trophic response of the older tissue is to inject non-toxic protease inhibitor(s) into the host tissue prior to MSC administration.…”
Section: Host Tissue Competencementioning
confidence: 99%
“…For example, in ischemic heart tissue, SDF-1α is the major chemokine attracting endogenous endothelial progenitors that express the SDF-1α receptor CXCR4 and home to the injured heart [82]. Accordingly, Zaruba et al recently described a small molecule-based regenerative strategy for treating myocardial infarction by recruiting endogenous bone marrow endothelial progenitors to the heart, which ultimately led to the generation of new blood vessels and improvement of heart functions [83]. The authors demonstrated that combined administration of granulocyte colony-stimulating factor (G-CSF) and the CD26 inhibitor Diprotin A can enhance the recruitment of CXCR4 positive stem cells to myocardium and improve survival and myocardial function by increasing neovascularization.…”
Section: Chemical Approaches Modulating In Vivo Regenerationmentioning
confidence: 99%